2018
DOI: 10.4103/ijdvl.ijdvl_526_17
|View full text |Cite
|
Sign up to set email alerts
|

End of the road for terbinafine? Results of a pragmatic prospective cohort study of 500 patients

Abstract: The effectiveness of terbinafine in dermatophytosis was abysmal in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 4 publications
6
40
1
Order By: Relevance
“…There have been concerns over increasing instances of failure to terbinafine in tinea corporis, tinea cruris and tinea faciei in the country. [ 103 104 ] Resistance to terbinafine due to mutations in the squalene epoxidase ( SQLE ) gene of Trichophyton interdigitale and T. rubrum has been documented in studies from Chandigarh and New Delhi. [ 59 60 ] High MIC's (Minimum inhibitory concentration) were observed and a higher dose (250 mg twice daily) or increased duration was found to be more effective in a study, hence the authors concluded that increased exposure to terbinafine, resulting in higher levels of the drug in the stratum corneum, could offset the higher MIC and the effect of SQLE mutation to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…There have been concerns over increasing instances of failure to terbinafine in tinea corporis, tinea cruris and tinea faciei in the country. [ 103 104 ] Resistance to terbinafine due to mutations in the squalene epoxidase ( SQLE ) gene of Trichophyton interdigitale and T. rubrum has been documented in studies from Chandigarh and New Delhi. [ 59 60 ] High MIC's (Minimum inhibitory concentration) were observed and a higher dose (250 mg twice daily) or increased duration was found to be more effective in a study, hence the authors concluded that increased exposure to terbinafine, resulting in higher levels of the drug in the stratum corneum, could offset the higher MIC and the effect of SQLE mutation to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the incidence of tinea corporis refractory to terbinafine treatment has been on the rise. 116 , 120 124 Terbinafine acts by inhibiting the enzyme squalene epoxidase, which is responsible for synthesis of ergosterol – an essential component of fungal cell wall. 122 Resistance to terbinafine has largely been attributed to point mutations in the squalene epoxidase target gene ( SQLE ).…”
Section: Treatmentmentioning
confidence: 99%
“…However, recent reports from the subcontinent has revealed an emerging trend of terbinafine resistance in Trichophyton species. A recent study from India demonstrated low cure rates of 2% at 2 weeks duration and 30.6% at 4 weeks in patients treated with terbinafine 3 . Terbinafine resistance in Trichophyton mentagrophytes complex and Trichophyton rubrum has been ascribed to point mutation in the squalene epoxidase (SE) gene, the gene essential for the ergosterol biosynthesis [4][5][6] .…”
mentioning
confidence: 97%